2019
DOI: 10.1556/030.66.2019.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an intestinal microbiota signature associated with hospitalized patients with diarrhea

Abstract: As an important global health challenge, diarrhea kills nearly two million people each year. Postinfectious irritable bowel syndrome (IBS) usually manifests itself as the diarrhea-predominant subtype. Small intestinal bacterial overgrowth has been observed more frequently in patients with IBS compared to healthy controls. However, the pathophysiology of IBS is not fully understood, and based on recent evidences, altered gut microbiota is involved in the pathogenesis of IBS. Therefore, we aimed to compare the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…According to clinical manifestations, IBS can be classified into the following subtypes: unclassified (IBS-U), mixed type (IBS-M), constipation-predominant (IBS-C), and diarrhea-predominant (IBS-D) ( 52 , 53 ), among which diarrhea type is the most prevalent. The gut microbiota of patients differs among different IBS subtypes, and it is speculated to be related to the typical constipation subtype ( 54 ). Studies have reported that patients with reduced IBS symptoms after FMT had lower depression scores, but the depression scores of patients who received placebo treatment did not change ( 55 ).…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…According to clinical manifestations, IBS can be classified into the following subtypes: unclassified (IBS-U), mixed type (IBS-M), constipation-predominant (IBS-C), and diarrhea-predominant (IBS-D) ( 52 , 53 ), among which diarrhea type is the most prevalent. The gut microbiota of patients differs among different IBS subtypes, and it is speculated to be related to the typical constipation subtype ( 54 ). Studies have reported that patients with reduced IBS symptoms after FMT had lower depression scores, but the depression scores of patients who received placebo treatment did not change ( 55 ).…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…Another case-control study by Tavasoli S et al [37] in 2019 investigated the abundance of Oxalobacter formigenes, Lactobacillus genus and Bifidobacterium genus in the gastrointestinal tract of the patients suffering from recurrent calcium kidney stone formation and normal population through quantitative real-time PCR. In addition, Mohammadzadeh N et al [38] in 2019 employed a quantitative real-time PCR technique to compare the gut microbiome profile of hospitalized patients with diarrhea to healthy individuals. Also, Heidarian F et al [39] in 2019 carried out a case-control study on the relative quantity of thirteen different bacterial families that were detected in the stool sample of patients with IBD and healthy participants through realtime PCR.…”
Section: General Features Of Iranian Microbiota Publicationsmentioning
confidence: 99%